PROBLEMATIKA PENDIDIKAN AGAMA DI MADRASAH - Peri Gunawan Peri (Asaatidzah, 2022)
This study aims to find out the early history of the establishment of madrasas in Indonesia and to find out the problems of Islamic religious education in madrasas. The method used in this research is library research, where the studies discussed are the results of searching and collecting information in the form of books, articles, or from previous research journals. Madrasah in Indonesia were established around the 20th century. The movement of Indonesian students who had returned from studying in the Middle East was the background for the establishment of madrasas in Indonesia, as well as a form of responsse by the Indonesian people to the Dutch East Indies colonizers where at that time the Dutch only allowed education if it was considered profitable. for them. There are several factors that cause problems in Islamic religious education, namely internal and external problems. Among them is the existence of a stigma among the people who think that religious education is not very important, the quality of PAI teachers is not good so that the delivery of religious material is less attractive to students. So that these two factors must be resolved seriously so that Islamic religious education in Indonesia runs well.